High capacity vanadium oxide electrodes: effective recycling through thermal treatment. Issue 10 (26th June 2019) - Huang, Jianping; Housel, Lisa M.; Wang, Lei; Bruck, Andrea M.; Quilty, Calvin D.; Abraham, Alyson; Lutz, Diana M.; Tang, Christopher R.; Kiss, Andrew; Thieme, Juergen; Takeuchi, Kenneth J.; Takeuchi, Esther S.; et al.
Abstract : The current paper demonstrates that thermal regeneration is an effective approach to recover material crystallinity, restore functional delivered capacity of the degraded phases, while retaining the integrity of the parent electrode. Abstract : This study demonstrates that thermal regeneration is an effective approach to convert degraded phases to functioning electroactive materials, restore functional delivered capacity and recover material crystallinity while retaining the integrity of the parent electrode. V2 O5 nanowires were synthesized through a facile hydrothermal method and used to fabricate V2 O5 /carbon nanotube (CNT) binder free electrodes. Discharge of the V2 O5 –CNT electrodes coupled with operando energy dispersive X-ray diffraction shows no evidence of phase segregation throughout the 150 μm thick binder free electrodes indicating full utilization of a thick electrode. When V2 O5 is highly electrochemically lithiated ( x > 2 in Li x V2 O5 ), irreversible phase transformation to ω-Li x V2 O5 was observed, accompanied by a capacity decrease of ∼40% over 100 cycles. A simple thermal treatment of the entire electrode results in a delivered capacity equal to or higher than the original value. Both phase conversion and an increase in material crystallinity as a result of thermal treatment are observed where structural analysis indicates the formation of Li1 V3 O8 . The electrode design approach with thick electrodes and functional thermal regeneration may provide a broader choice of electroactive materials through decreasing the environmental burden by extending the lifetime of energy storage systems.